Comparison of the Growth and Development of Green Spinach (Amaranthus hybridus L.) under Soil Conditions from the Java and Kalimantan Regions - Riannisa'a Shafira; Fitria Alfiyah Hastuari; Anindya Aulya Andayani; Rofina Mbale Role; Meti Indrowati (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to compare the growth of green spinach (Amaranthus hybridus L.) cultivated in two different soil types originating from Java and Kalimantan, and to examine the effect of soil pH on plant height. The experiment was conducted over a 21-day period (3–24 November 2025) using a comparative experimental design with a total of eight samples, consisting of four plants in each treatment group. The parameters observed included soil pH, plant height, number of leaves, leaf width, and leaf color. Environmental variables—such as light intensity, water volume, pot size, and seed quantity—were controlled to ensure consistent experimental conditions. The data were analyzed using statistical assumption tests, including the Shapiro–Wilk normality test and Levene’s homogeneity test, followed by linear regression analysis and analysis of covariance (ANCOVA). The results indicated that the data were normally distributed (p = 0.328) and homogeneous (p = 0.575). Regression analysis showed that soil pH had a significant effect on plant height (p = 0.026), whereas soil type did not have a significant effect after controlling for soil pH (ANCOVA, p = 0.089). The mean difference in plant height between soils from Java and Kalimantan was 2.90 cm; however, this difference was not statistically significant. These findings suggest that the growth of green spinach—particularly plant height—is more strongly influenced by environmental factors, especially soil pH, than by differences in soil origin.